2021
DOI: 10.3390/plants10112321
|View full text |Cite
|
Sign up to set email alerts
|

Carotenoids and Apocarotenoids in Planta: Their Role in Plant Development, Contribution to the Flavour and Aroma of Fruits and Flowers, and Their Nutraceutical Benefits

Abstract: Carotenoids and apocarotenoids are diverse classes of compounds found in nature and are important natural pigments, nutraceuticals and flavour/aroma molecules. Improving the quality of crops is important for providing micronutrients to remote communities where dietary variation is often limited. Carotenoids have also been shown to have a significant impact on a number of human diseases, improving the survival rates of some cancers and slowing the progression of neurological illnesses. Furthermore, carotenoid-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 352 publications
0
28
0
1
Order By: Relevance
“…As a result of the degradation of carotenoids, their content is strongly correlated with the progression of tomato fruits' ripening, mainly due to the accumulation of lycopene, even if their production is not linear and their overall concentration remains low [31]. Although they are present in very low concentrations, they have a primary role in conferring floral/fruity notes to tomatoes and increasing product appreciation [10,46,47].…”
Section: Carotenoid Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the degradation of carotenoids, their content is strongly correlated with the progression of tomato fruits' ripening, mainly due to the accumulation of lycopene, even if their production is not linear and their overall concentration remains low [31]. Although they are present in very low concentrations, they have a primary role in conferring floral/fruity notes to tomatoes and increasing product appreciation [10,46,47].…”
Section: Carotenoid Derivativesmentioning
confidence: 99%
“…In ripe tomatoes, the cytosolic enzymes LeCCD1A and LeCCD1B perform an oxidative cleavage of multiple linear carotenoids, either at the 5,6, 7,8, or 9,10 positions, and cyclic carotenoids at the 9,10 position. This leads to the biosynthesis of dialdehydes and ketones, forming several C13 volatiles such as pseudoionone, β-ionone, 6-methyl-5-hepten-2-one, β-damascenone and geranylacetone, which is reported to be generated by the oxidative cleavage of phytoene, phytofluene, ζ-carotene, and neurosporene [18,26,[47][48][49]. In tomatoes, the LeCCD1 cleavage of lycopene at the 5,6 position leads to 6-methyl-5-hepten-2-one, which is associated with the tomato-like flavour and sweet floral aroma of tomatoes [48,50].…”
Section: Carotenoid Derivativesmentioning
confidence: 99%
“…The treatment with GA also influences the other hormonal pathways, since the treated ovaries showed a small but significant increase of IAA at 3 and 14 DAT, and a significant drop of ABA. Indeed, PbARF5, PbARF6, PbARF18, PbARF19-like , and Pb9-cis-epoxycarotenoid dioxygenase (NCED), which encode key enzymes in the steps for the synthesis of ABA (Schwartz et al 1997 , 2003 ; Simkin 2021 ), have been found to be down-regulated both in the GA 4+7 -treated and pollinated ovaries. Therefore, the model proposed by Liu and collaborators suggests that GA 4+7 mimics the effect that pollination has in changing the hormones levels, causing a downstream change of expression of gene involved in different aspects of the transition from ovary to fruit (Liu et al 2018 ) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Natural pigments can be derived from carotenoid group compounds abundant in plants. Carotenoids are found in chloroplasts and are responsible for the plant's aroma, flavor, and colors of yellow, bright red, and orange (Cazzonelli, 2011;Hermanns et al, 2020;Simkin, 2021). Carotenoids are soluble in a wide range of organic solvents, including alcohol group solvents (Kultys & Kurek, 2022;Saini & Keum, 2018).…”
Section: Introductionmentioning
confidence: 99%